Evaluation of Reader Services in University Libraries in Ghana: Beyond the Client-centred Approach, What Next? - Osei, Isaac (Ghana Library Journal, 1996)
Facet studies of various degrees employing the client-centred approach have been undertaken to evaluate the effectiveness of reader services of university libraries in Ghana. A school of thought observes that results from the client-centred approach cannot be taken seriously because they are imprecise, incomplete and inadequate to assess interaction between various operations and services and between related inputs and outputs. In its place, the objective method which comprises specific indicators of performance is suggested. This paper seeks to go beyond the client-centred approach, which has characterised library evaluation in Ghana, to explore and examine the suitability of the objective method as an alternative measure for evaluation. It is concluded that neither method enjoy universal acceptance among library evaluators. Either method, with fewest practical weaknesses, could be adopted.